2015
DOI: 10.1371/journal.pgen.1004935
|View full text |Cite|
|
Sign up to set email alerts
|

Partially Redundant Enhancers Cooperatively Maintain Mammalian Pomc Expression Above a Critical Functional Threshold

Abstract: Cell-specific expression of many genes is conveyed by multiple enhancers, with each individual enhancer controlling a particular expression domain. In contrast, multiple enhancers drive similar expression patterns of some genes involved in embryonic development, suggesting regulatory redundancy. Work in Drosophila has indicated that functionally overlapping enhancers canalize development by buffering gene expression against environmental and genetic disturbances. However, little is known about regulatory redun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
147
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 110 publications
(160 citation statements)
references
References 58 publications
11
147
2
Order By: Relevance
“…Similar treatment effects were observed in Pomc Δ2 mice, which maintain functional POMC activity (Lam et al., 2015) despite a ~40% reduction in constitutive ARC Pomc expression at the time of necropsy (Figure 2c). In Pomc wt and Pomc Δ2 , this change in body mass occurred in conjunction with an immediate decline in food intake (Figure 2d) that was followed by a slow rebound in energy intake by week 3 (Figure 2e).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Similar treatment effects were observed in Pomc Δ2 mice, which maintain functional POMC activity (Lam et al., 2015) despite a ~40% reduction in constitutive ARC Pomc expression at the time of necropsy (Figure 2c). In Pomc wt and Pomc Δ2 , this change in body mass occurred in conjunction with an immediate decline in food intake (Figure 2d) that was followed by a slow rebound in energy intake by week 3 (Figure 2e).…”
mentioning
confidence: 95%
“…Deletion of nPE2, nPE1, or insertion of a transcription‐blocking neo selection cassette into the vicinity of the two hypothalamic neuronal Pomc enhancers reduces hypothalamic Pomc expression to ~80%, ~30%, or ~2% of wild‐type controls, respectively (Lam et al, 2015). A reduction in hypothalamic Pomc expression at or below ~30% of wild‐type controls in these mice results in a functional loss of Pomc ‐mediated regulation of body mass (Bumaschny et al., 2012; Lam et al., 2015; Zhan et al., 2013). Therefore, we hypothesized that if 17α‐E2 were to act selectively by increasing hypothalamic Pomc expression, the treatment effects on body mass and food intake would be disrupted in mutant mice lacking nPE1 ( Pomc Δ1 ) or those containing the Pomc transcription‐blocking neo selection cassette ( Pomc neo ).…”
mentioning
confidence: 99%
“…Expression studies in transgenic mice showed that nPE1 and nPE2 drive completely overlapping spatiotemporal enhancer activities to the ∼3,000 POMC neurons present in the mouse ventromedial hypothalamus during embryogenesis as well as in adulthood (16) and only the concurrent removal of both enhancers from the mouse Pomc locus by targeted mutagenesis reduced Pomc expression to very low levels, leading to hyperphagia and early-onset obesity (17). Interestingly, nPE1 and nPE2 are unrelated sequences with distinct evolutionary origins; whereas nPE2 is derived from the exaptation (cooption) of a CORE-short interspersed nuclear element (SINE) retroposon in the lineage leading to mammals more than 166 million years ago (Mya) (18), nPE1 is a placental mammal novelty derived from the exaptation of a LTR-containing a mammalian apparent LTR retroposon that occurred between 150 and 90 Mya (16).…”
mentioning
confidence: 99%
“…We have recently identified conserved C/ATTA motifs that might be recognized by homeodomain-containing transcription factors (HDTFs) within nPE2 and nPE1, which are essential for driving reporter gene expression to POMC neurons (17). Because nPE1 and nPE2 are functional analogs, it is conceivable that these sequences recruit a common, yet unidentified TF able to transactivate Pomc in the hypothalamus.…”
mentioning
confidence: 99%
See 1 more Smart Citation